STRATEGI GURU YDK DALAM MENANGANI ANAK ADHD DI SDN 2 TUTUP: STUDI KASUS - Yanita Sari; Liftiah; Ali Formen (STKIP Subang, 2026)
Children with Attention Deficit Hyperactivity Disorder (ADHD) in elementary schools often face difficulties in sustaining attention, controlling impulses, and engaging in social interactions. Teachers, as the frontline of learning, frequently lack appropriate strategies, especially in schools without special assistant teachers. This study aims to analyze teachers' strategies in managing ADHD children at SDN 2 Tutup through a case study of a second-grade student named ADA. A qualitative approach with a case study design was employed. Data were collected through passive participatory observation (four sessions), semi-structured interviews with Teacher YDK and ADA's parents, and documentation of lesson plans and anecdotal records. Data analysis followed the Miles, Huberman, and Saldaña interactive model. The results showed that Teacher YDK implemented six main strategies: strategic seating arrangement, reduction of visual distractions, single-step short instructions, use of simple visual media, positive reinforcement (specific praise and star stickers), and movement breaks every 20 minutes. These strategies successfully increased ADA's attention span from 3–5 minutes to 10–12 minutes, reduced impulsive behaviors by 50%, and helped ADA complete simple tasks more independently. The main obstacles included the lack of a special assistant teacher, limited facilities, and parental inconsistency. This study recommends systemic support through teacher training and the provision of inclusive facilities.